Assessing the spatial heterogeneity in black-white differences in optimal cardiovascular health and the impact of individual- and neighborhood-level risk factors: The Multi-Ethnic Study of Atherosclerosis (MESA). (June 2020) - Tabb, Loni Philip; McClure, Leslie A.; Ortiz, Angel; Melly, Steven; Jones, Miranda R.; Kershaw, Kiarri N.; Roux, Ana V. Diez
Highlights: Cardiovascular health (CVH) is examined, which focuses on health behaviors and factors. Spatial variation in CVH was explored using a unique, diverse population-based cohort study. Black-white disparities in CVH vary within and across 5 US cities. Blacks have decreased odds of optimal and overall cardiovascular health. Individual- and neighborhood-level risk factors, both subjective and objective measures, reduced varying disparities. Abstract: Racial disparities in cardiovascular health (CVH) continue to remain a public health concern in the United States. We use unique population-based data from the Multi-Ethnic Study of Atherosclerosis cohort to explore the black-white differences in optimal CVH. Utilizing geographically weighted regression methods, we assess the spatial heterogeneity in black-white differences in optimal CVH and the impact of both individual- and neighborhood-level risk factors. We found evidence of significant spatial heterogeneity in black-white differences that varied within and between the five sites. Initial models showed decreased odds of optimal CVH for blacks that ranged from 60% to 70% reduced odds – with noticeable variation of these decreased odds within each site. Adjusting for risk factors resulted in reductions in the black-white differences in optimal CVH. Further understanding of the reasons for spatial heterogeneities in black-white differences in nationally representative cohorts may provide important clues regarding the drivers of these differences.